Regulatory effects and mechanisms of exercise on activation of brown adipose tissue (BAT) and browning of white adipose tissue (WAT) - Haijun Dong; Man Qin; Peng Wang; Shufan Li; Xing Wang (Adipocyte, 2023)
ABSTRACTExercise is a universally acknowledged and healthy way to reducing body weight. However, the roles and mechanisms of exercise on metabolism of adipose tissue remain largely unclear. Adipose tissues include white adipose tissue (WAT), brown adipose tissue (BAT) and beige adipose tissue (BeAT). The main function of WAT is to store energy, while the BAT and BeAT can generate heat and consume energy. Therefore, promotion of BAT activation and WAT browning contributes to body weight loss. To date, many studies have suggested that exercise exerts the potential regulatory effects on BAT activation and WAT browning. In the present review, we compile the evidence for the regulatory effects of exercise on BAT activation and WAT browning and summarize the possible mechanisms whereby exercise modulates BAT activation and WAT browning, including activating sympathetic nervous system (SNS) and promoting the secretion of exerkines, with special focus on exerkines. These data might provide reference for prevention or treatment of obesity and the related metabolic disease through exercise.